2014
DOI: 10.5935/0103-1104.20140070
|View full text |Cite
|
Sign up to set email alerts
|

A dinâmica familiar sob a ótica do profissional da Estratégia Saúde da Família

Abstract: rESUMo A efetivação da Atenção Básica exige a superação das práticas exclusivamente voltadas para a doença e para o cuidado individual, com vistas ao incremento de ações interdisciplinares e integrais destinadas ao cuidado familiar e coletivo. Este estudo objetivou investigar o grau de atenção que, em suas práticas, os profissionais de uma equipe da Estratégia Saúde da Família, na cidade do Rio de Janeiro, dedicam às dinâmicas relacionais das famílias. A realização de entrevistas semiestruturadas e de imersões… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…There is no monitoring of sexual partners by the centers and the professionals are worried about the involvement of the CHA in this process. In Rio de Janeiro, Brazil, a previous study showed that such worry is mainly related to the fact that the CHA lives in the same area as the patient they serve and have personal relationships with them, which could compromise the uptake and confidentiality of patient’s information [30]. It should be noted that the CHA is a member of the Family Health Strategy team and difficulties in dealing with issues arising from STI diagnosis are not specific to this category [31].…”
Section: Discussionmentioning
confidence: 99%
“…There is no monitoring of sexual partners by the centers and the professionals are worried about the involvement of the CHA in this process. In Rio de Janeiro, Brazil, a previous study showed that such worry is mainly related to the fact that the CHA lives in the same area as the patient they serve and have personal relationships with them, which could compromise the uptake and confidentiality of patient’s information [30]. It should be noted that the CHA is a member of the Family Health Strategy team and difficulties in dealing with issues arising from STI diagnosis are not specific to this category [31].…”
Section: Discussionmentioning
confidence: 99%
“…The Brazilian Ministry of Health and international organisations, such as the World Health Organization (WHO) and United Nations Children's Foundation (UNICEF), established the Baby-Friendly Hospital Initiative (BFHI), whose objective is to aware healthcare professionals about the importance of breastfeeding. The aim of such an initiative is to increase the rates of breastfeeding across the world 8,9 , which are still low 3,[10][11][12][13] , by alerting on the necessity of a co-ordinated work for qualification of healthcare professionals and integration of healthcare services 14 . The Breastfeeding-Friendly Primary Care Initiative (BFPCI), proposed by the Ministry of Health, was launched by the Rio de Janeiro State Secretary of Health with the aim of improving the rates of breastfeeding and promoting support to nursing mothers in the Basic Health Units (BHUs).…”
Section: Introductionmentioning
confidence: 99%
“…This initiative proposes that BHUs, in conjunction with hospitals, implement the "Ten Steps to Successful Breastfeeding" and qualify the healthcare professionals 15 , with the latter being crucial. It is fundamental to listen to the healthcare professionals in the evaluation process so that strategies can be adequately planned in order to improve the quality of the services provided 6,14 . The community health worker (CHW) plays an important role in the successful breastfeeding as he or she is the healthcare professional who is next to the nursing mothers, acting as an integrating link between healthcare staff and community 14,16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation